Manajemen Edukasi Dengan Mengurangi Nyeri Pada Kasus Low Back Pain Untuk Meningkatkan Produktivitas Petani Di Desa Pelemgadung, Sragen, Jawa Tengah - Ernanda Zainovita; Ronald Rizal Shidiq; Raden Shafira Saniyyah Ramadhani; Zara Sugiyarti; Siti Fadhilah; Rahma Septiara; Devia Putri Agnesia; Heru Purnomo; Tomiana Tomiana; Ilham Yugantara; Dwi Rosella Komala Sari; Suryo Saputra Perdana (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Pelemgadung Village is located in Sragen Regency, Central Java, where the majority of the population makes their living as farmers. According to the results of situation analysis and data collection, it was found that low back pain is one of the conditions that often occurs in the village. Low back pain is a musculoskeletal disorder that arises due to a static body position while working, resulting in pain in the lower back. The aim of this activity is to increase farmers’ understanding and knowledge of reducing lower back pain. The method used was education about low back pain using leaflets as a health promotion medium, as well as distributing pre- and post- questionnaires to assess farmers’ knowledge about low back pain. The results of the questionnaire show an increase in farmers’ understanding, which can be seen from the number of participants with the highest scores. During the pre-test, 24 people achieved the highest score, while in the post-test, the number increased to 35 people. Based on the education that has been carried out, it can be concluded that there has been an increase in farmers’ understanding of low back pain and how to overcome this condition.